2005
DOI: 10.1002/cbm.29
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and its relevance in a seven-year admission cohort to an English national adolescent medium secure health service unit

Abstract: Our findings confirm both a high overall proportion of young people from ethnic minorities using a national medium secure hospital service and considerable ethnic diversity within that. They are discussed in the context of one relevant national government initiative for improving responses to minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This investigation is against the background of a well-established literature on biases in the identification and treatment of other psychiatric groups across ethnic groups, [1][2][3][4][5][6][7] regardless of actual levels of psychopathology or comparability of treatment outcomes. 19 The referrals were substantially different to what might be expected given the local population statistics, with non-white patients being far less likely to be referred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation is against the background of a well-established literature on biases in the identification and treatment of other psychiatric groups across ethnic groups, [1][2][3][4][5][6][7] regardless of actual levels of psychopathology or comparability of treatment outcomes. 19 The referrals were substantially different to what might be expected given the local population statistics, with non-white patients being far less likely to be referred.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the United Kingdom, African-Caribbeans, and Black Africans are at especially high risk for both schizophrenia and mania. 1 These groups are over-represented in psychiatric in-patient populations in the United Kingdom, 2,3 and levels of unmet needs and adverse care pathways are more common in this group than in their white counterparts. [3][4][5][6] In contrast, in the United Kingdom, prevalence rates of detection and management of common psychiatric disorders are comparable to those of white patients for some minority groups (AfroCaribbean) though not for others (Black African).…”
Section: Introductionmentioning
confidence: 98%
“…The majority of those from African backgrounds in this study had a refugee background and there were high levels of social and family adversity, migration, poverty and family separation (Tolmac & Hodes, 2004). In offering an explanation for these findings, the authors state that a poorer social support network and an increased level of adversities could result in a greater need for admission, while also claiming that the results may also be due simply to a higher prevalence of psychosis in ethnic minority adolescents (Chowdhury, Whittle, McCarthy, Bailey, & Harrington, 2005).…”
Section: Developmental Understanding Of Violencementioning
confidence: 92%
“…3 highrated (6,24,25) and 1 medium-rated study (22) concluded that psychotic-based admissions or prescription rates in minorities were not different to the White population. Contrastingly, 4 low-rated (19,(26)(27)(28)) and 2 medium-rated studies (14,29) found that psychotic conditions were more frequent among the Black population. Therefore, it appears that the prevalence of psychotic disorders is inconclusive.…”
Section: Prevalence Of Psychiatric Disordersmentioning
confidence: 93%